Qualitative inquiry & research design : choosing among five approaches - Creswell, John W. 4 0 16; 5 (Thousand Oaks, California : Sage Publications, 2007)
Describes five approaches to qualitative research--narrative research, phenomenology, grounded theory, ethnography, and case study--and provides specific steps for doing research within each approach, including examples from education, sociology, psychology, and human services.
Includes bibliographical references and indexes.
Professional.
Keywords: 2 -- 0; 6; Methodology. -- Social sciences; 20; 2